The first Chief Justice : John Jay and the struggle of a new nation - Dillon, Mark C. (State University of New York Press, 2022)
"Chronicles the efforts of the first Chief Justice of the US Supreme Court to establish a federal court system during the country's uncertain early years"-- Provided by the publisher.
Keywords: Jay, John, -- 1745-1829.; United States. -- Supreme Court -- Officials and employees -- Biography.; United States. -- Supreme Court -- History.; United States. -- Supreme Court -- Cases -- History.; États-Unis. -- Supreme Court -- Fonctionnaires -- Biographies.; États-Unis. -- Supreme Court -- Histoire.; États-Unis. -- Supreme Court -- Jurisprudence -- Histoire.; Jay, John, -- 1745-1829; United States. -- Supreme Court; Judges -- United States -- Biography.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.; New York (State) -- Politics and government -- To 1775.; Juges -- États-Unis -- Biographies.; États-Unis -- Politique et gouvernement -- 1775-1783.; États-Unis -- Politique et gouvernement -- 1783-1809.; New York (État) -- Politique et gouvernement -- Jusqu'à 1775.; Employees; Judges; Politics and government; New York (State); United States; Biography; Biographies; History; Biographies.